Pengaruh Kepatuhan Wajib Pajak, Kualitas Pelayanan dan Sanksi Pajak terhadap Upaya Meningkatkan Penerimaan Pajak Kendaraan Bermotor Selama Masa Pandemi Covid-19 pada Kantor SAMSAT Wilayah Jakarta Timur Tahun 2021 - Diah Rana Zhafira (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
Tax revenue is one of the sources of state financing. One of the government's efforts to increase tax revenue is the self-assessment system to encourage taxpayers to become obedient in paying taxes. It was necessary because increasing tax revenues will increase the productivity of a country. This study aimed to analyze motorized vehicle taxpayer compliance and to find out the obstacles, stimuli, and strategies used to increase local tax revenues in the East Jakarta One Roof System (Samsat). The research theory used was the theory of efforts to increase tax revenue by Siti Kurnia Rahayu (2017). The research method used was a quantitative approach with a descriptive research type. The data collection techniques were secondary data from the East Jakarta Samsat office and primary data obtained from questionnaires and observations. The sampling technique was simple random sampling containing 1,190,763 two-wheeled motorized vehicle taxpayers registered in the East Jakarta Samsat until 2021. The results showed that taxpayer compliance had no partial significant effect on increasing tax revenue with the result of 0.163 > 0.05, while the quality of service partially had a significant effect on increasing tax revenue with the result of 0.015 < 0.05, and tax sanctions partially had a significant effect on increasing tax revenue with the result of 0.000 < 0.05.